The ghost illusion - Martin, Kat (Kensington Publishing Corp., 2023)
"Eve St. Clair desperately needs help sorting reality from her fearful imaginings when ghostly voices seem to haunt the Victorian house in Sunderland, England, that she inherited from her uncle. Online research leads to a group that claims to offer just the aid she's seeking. But can Ransom King's handpicked team of investigators truly banish Eve's night terrors? Since the deaths of his wife and daughter, Seattle billionaire Ransom King has devoted himself to researching parapsychology and debunking the frauds who prey upon the bereaved. But Eve is a psychologist herself, clearly sane, and her sincerity is palpable. King senses a very real danger stalking the beautiful divorcée. As his interest in her case turns deeply personal, he will move heaven and earth to uncover the truth--no matter how shocking--and save the woman he loves"--